2022
DOI: 10.3844/ojbsci.2022.279.286
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of Bipolaris Sorokiniana Isolated from Spring Barley Leaves to Survive in Plant Residuals of Different Crops

Abstract: Spring barley is an important high-value crop globally.However, it is highly susceptible to soil-borne diseases in Kazakhstan and the world. Bipolaris sorokiniana (Sacc.) Shoemaker is the most important soil-borne pathogen that causes root rot and spot blotch diseases in cereal crops. This study aimed to evaluate the ability of B. sorokiniana isolated from spring barley leaves to survive in plant residuals of different crops. The fungus was isolated from spring barley leaves from the Zholbarys agro farm of Ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…They considered the pathogenicity of common root rot in triticale caused by B. sorokiniana and found that it causes a reduction of productive business, crop thinning, reduction of earliness and grain weight, and a decrease in grain quality (Özer et al, 2020b). Studies evaluated the ability of B. sorokiniana isolated from spring barley leaves to survive in plant residuals of different crops (Dutbayev et al, 2022). However, there is not enough information about the severity of common root rot and the impact of the degree of disease damage on plant productivity in Kazakhstan.…”
Section: Introductionmentioning
confidence: 99%
“…They considered the pathogenicity of common root rot in triticale caused by B. sorokiniana and found that it causes a reduction of productive business, crop thinning, reduction of earliness and grain weight, and a decrease in grain quality (Özer et al, 2020b). Studies evaluated the ability of B. sorokiniana isolated from spring barley leaves to survive in plant residuals of different crops (Dutbayev et al, 2022). However, there is not enough information about the severity of common root rot and the impact of the degree of disease damage on plant productivity in Kazakhstan.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of experimental results of urban environment safety demonstrates that major portion of the investigations is devoted to determination of influence of negative chemical factors (toxic matters) on plants and human health [10][11][12][13]. This could be attributed only to the fact that high concentrations of toxic matters in air can influence on major portion of inhabitants [14], initiate acute intoxications, and require for significant resources of health care system to eliminate the consequences [15].…”
Section: Introductionmentioning
confidence: 99%